2020
DOI: 10.1002/ajpa.24108
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related site‐specific modifications in diaphyseal structural properties of the human fibula: Furrows and cross‐sectional geometry

Abstract: Objectives: Fibular structure is related to locomotor behavior, which allows an exploration of mobility in past human populations with diaphyseal cross-sectional geometry (CSG). However, bone structure depends on age-related changes. Nonmechanical alterations can affect biomechanical investigations. In this study, we examined how the cortical area and the variables used as functional markers in the fibular diaphysis (i.e., CSG and furrows) change with aging. We predict classic and specific modifications, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…EMG studies have shown that in humans, peroneal muscles are more active when everting the inverted foot (Bavdek et al, 2018), suggesting their essential role in laterally stabilizing the inverted ankle joint while traversing a medially inclined ramp. Peroneal muscles in humans also have been reported to form concave furrows along the anterior fibular surface of the diaphysis in correlation with a combined effect of age and mechanical loading (Chevalier & Tignères, 2020; Hagihara & Nara, 2016). While no specific studies on peroneal anatomy and electromyography were performed on great apes, previous research on human peroneal muscles activation and fibular diaphyseal anatomy (Bavdek et al, 2018; Chevalier & Tignères, 2020) allow us to suggest that the lack of a concavity in the anterior surface of the fibula is indicative of lower peroneal activity in humans than in great apes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EMG studies have shown that in humans, peroneal muscles are more active when everting the inverted foot (Bavdek et al, 2018), suggesting their essential role in laterally stabilizing the inverted ankle joint while traversing a medially inclined ramp. Peroneal muscles in humans also have been reported to form concave furrows along the anterior fibular surface of the diaphysis in correlation with a combined effect of age and mechanical loading (Chevalier & Tignères, 2020; Hagihara & Nara, 2016). While no specific studies on peroneal anatomy and electromyography were performed on great apes, previous research on human peroneal muscles activation and fibular diaphyseal anatomy (Bavdek et al, 2018; Chevalier & Tignères, 2020) allow us to suggest that the lack of a concavity in the anterior surface of the fibula is indicative of lower peroneal activity in humans than in great apes.…”
Section: Discussionmentioning
confidence: 99%
“…Peroneal muscles in humans also have been reported to form concave furrows along the anterior fibular surface of the diaphysis in correlation with a combined effect of age and mechanical loading (Chevalier & Tignères, 2020; Hagihara & Nara, 2016). While no specific studies on peroneal anatomy and electromyography were performed on great apes, previous research on human peroneal muscles activation and fibular diaphyseal anatomy (Bavdek et al, 2018; Chevalier & Tignères, 2020) allow us to suggest that the lack of a concavity in the anterior surface of the fibula is indicative of lower peroneal activity in humans than in great apes. This finding agrees with previous studies that suggested a connection between a wider peroneal groove and fossa, observed at the distal fibular extremity, and larger, powerful peroneal muscles (Marchi, 2015b; Marchi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation